Forensic Odontology and its applicability in processing crime scenes and other catastrophic events - Chango-Iza, Roberto. D. (2016)
In recent years, forensic dentistry reaches critical importance worldwide, getting through certain procedures to estimate, time and date of death of a person, facilitating the resolution of multiple and complicated cases of death. The procedures employed also allow the lifting of fingerprints by applying techniques; Queiloscopía, Biting, Registration Rugas Palatine, providing thus a great contribution in the Criminal Investigation in its first phase Inquest, within which the processing of the scene seeks to collect evidence and binding evidence the fact that subsequently through a chain of custody is transferred to the laboratory where the evidence and evidence will be studied, becoming media expert evidence to identify the fact and authorship of an allegedly criminal act, thus presents a collection of literature concerning the subject that seeks to inform the general practice dentist on terminology, procedures and other related forensic sciences in order to inform and update their knowledge about it.